Using a barcoded AAV capsid library to select for clinically relevant gene therapy vectors - Pekrun, Katja (JCI Insight, 2019)
While gene transfer using recombinant adeno-associated viral (rAAV) vectors has shown success in some clinical trials, there remain many tissues that are not well transduced. Because of the recent success in reprogramming islet-derived cells into functional β cells in animal models, we constructed 2 highly complex barcoded replication competent capsid shuffled libraries and selected for high-transducing variants on primary human islets. We describe the generation of a chimeric AAV capsid (AAV-KP1) that facilitates transduction of primary human islet cells and human embryonic stem cell–derived β cells with up to 10-fold higher efficiency compared with previously studied best-in-class AAV vectors. Remarkably, this chimeric capsid also enabled transduction of both mouse and human hepatocytes at very high levels in a humanized chimeric mouse model, thus providing a versatile vector that has the potential to be used in both preclinical testing and human clinical trials for liver-based diseases and diabetes.